Upper-limb biomechanical analysis of wheelchair transfer techniques in two toilet configurations. (June 2018) - Tsai, Chung-Ying; Boninger, Michael L.; Bass, Sarah R.; Koontz, Alicia M.
Abstract: Background: Using proper technique is important for minimizing upper limb kinetics during wheelchair transfers. The objective of the study was to 1) evaluate the transfer techniques used during toilet transfers and 2) determine the impact of technique on upper limb joint loading for two different toilet configurations. Methods: Twenty-six manual wheelchair users (23 men and 3 women) performed transfers in a side and front wheelchair-toilet orientation while their habitual transfer techniques were evaluated using the Transfer Assessment Instrument. A motion analysis system and force sensors were used to record biomechanical data during the transfers. Findings: More than 20% of the participants failed to complete five transfer skills in the side setup compared to three skills in the front setup. Higher quality skills overall were associated with lower peak forces and moments in both toilet configurations (−0.68 < r < −0.40, p < 0.05). In the side setup, participants who properly placed their hands in a stable position and used proper leading handgrips had lower shoulder resultant joint forces and moments than participants who did not perform these skills correctly ( p ≤ 0.04). In the front setup, positioning the wheelchair within three inches of the transfer target was associated with reduced peak trailing forces and moments across all three upper limb joints ( p = 0.02). Interpretation: Transfer skills training, making toilet seats level with the wheelchair seat, positioning the wheelchair closer to the toilet and mounting grab bars in a more ideal location for persons who do sitting pivot transfers may facilitate better quality toilet transfers. Highlights: Using proper transfer technique reduces upper limb loading during toilet transfers. Transfer techniques were more appropriate for the front versus side toilet setup. Handgrip, head-hips relationship, and chair positioning are important in transfers. Grab bar location may not be ideal for people who use their arms only to transfer. A toilet seat riser is recommended to make wheelchair to toilet transfers level.